Effectiveness of Ginger in Treating Nausea and Vomiting of Pregnancy - Ahmad Ramadhanu (HM Publisher, 2021)
Nausea and vomiting in pregnancy (NVP) is one of the common main complaint in pregnancy. NVP can be a significant burden to the patient, make a decrease in quality of life, pregnancy threatening or even worse can lead to nutritional loss and death. NVP diagnosed when in first trimester of pregnancy and the other possible cause of NVP is excluded. Management of NVP is included maintaining hydration, nutrition, and lifestyle modification. Also avoiding the smells, food, or activity that can cause nause are necessary. There are some methods to treat NVP including pharmalogical or non-pharmalogical. The non-pharmalogical approach is change nutritional habits, lifestyle and medications. Several pharmalogical agents that can be used to relief the symptoms of NVP are pyridoxine, anti- histamines, metoclopramide, pyridoxine/doxylamine, promethazine and metoclopramide. Some patients also want to try more “natural” medications for NVP like ginger. The pharmacological activity is thought to stand in the pungent principles (gingerols and shogaols) and volatile oils (sesquiterpenes and monoterpenes). The true mechanism of action of ginger is probable to be a gastric effect, to increase tone and peristaltic due to anticholinergic and antiserotonin act. Ginger acts straight to the digestive tract and avoids the CNS side effects common to centrally acting antiemetics. Ginger is available in capsule or syrup form or in candy, cookies, beer, tinctures, teas, sodas, and jam. Nowadays, true dosing is available only if one uses standardized extracts; however, women may choose to use another form of ginger.